2005
DOI: 10.1103/physrevb.71.214106
|View full text |Cite
|
Sign up to set email alerts
|

In situhigh-pressure synchrotron x-ray diffraction study ofSc2W3O12at up to 10 GPa

Abstract: Sc 2 W 3 O 12 is known to display both negative thermal expansion and significant Sc 3+ conductivity. Monochromatic synchrotron x-ray powder diffraction was used to study Sc 2 ͑WO 4 ͒ 3 at pressures up to 10 GPa in diamond anvil cells. Nitrogen and isopropanol were both used as pressure transmitting media. A phase transition from orthorhombic ͑Pnca͒ to monoclinic ͑P2 1 / a͒ symmetry was observed at ϳ0.3 GPa with a volume reduction of ϳ1.7%. A second crystalline to crystalline phase transition was seen at ϳ2.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 84 publications
1
22
0
Order By: Relevance
“…The low densities and highly flexible frameworks of many NTE materials, combined with the presence of lattice modes that soften on volume reduction [10][11][12][13][14][15][16] predispose them to interesting highpressure behavior. Crystalline to crystalline phase transitions have been observed at high pressure in cubic ZrW 2 O 8 [11,12,[17][18][19][20], cubic HfW 2 O 8 [13,21], cubic ZrMo 2 O 8 [22,23], cubic HfMo 2 O 8 [22], ZrV 2 O 7 [24], Sc 2 W 3 O 12 [25], Sc 2 Mo 3 O 12 [26,27] and Al 2 W 3 O 12 [27][28][29]. Additionally, pressure induced amorphization (PIA) has been seen for ZrMo 2 O 8 [22,23], ZrW 2 O 8 [30], Sc 2 W 3 O 12 [31], Sc 2 Mo 3 O 12 [32] and Lu 2 W 3 O 12 [33] at low pressures.…”
Section: Introductionmentioning
confidence: 99%
“…The low densities and highly flexible frameworks of many NTE materials, combined with the presence of lattice modes that soften on volume reduction [10][11][12][13][14][15][16] predispose them to interesting highpressure behavior. Crystalline to crystalline phase transitions have been observed at high pressure in cubic ZrW 2 O 8 [11,12,[17][18][19][20], cubic HfW 2 O 8 [13,21], cubic ZrMo 2 O 8 [22,23], cubic HfMo 2 O 8 [22], ZrV 2 O 7 [24], Sc 2 W 3 O 12 [25], Sc 2 Mo 3 O 12 [26,27] and Al 2 W 3 O 12 [27][28][29]. Additionally, pressure induced amorphization (PIA) has been seen for ZrMo 2 O 8 [22,23], ZrW 2 O 8 [30], Sc 2 W 3 O 12 [31], Sc 2 Mo 3 O 12 [32] and Lu 2 W 3 O 12 [33] at low pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Many compositions are known to form with structures related to that of orthorhombic Sc 2 W 3 O 12 [1][2][3][4]. They typically display anisotropic volume NTE while orthorhombic, but are susceptible to symmetry lowering phase transitions [5], with a concomitant loss of NTE, on cooling or modest compression [6][7][8][9]. The Sc 2 W 3 O 12 framework is amenable to a wide range of substitutions beyond the simple replacement of Sc 3+ with other trivalent ions; for example, materials such as A 2 (MO 4 )(PO 4 ) 2 (A-Zr or Hf; M-W or Mo) [10][11][12][13], (HfMg)(WO 4 ) 3 [14][15][16][17], and Zr 2 (SO 4 )(PO 4 ) 2 [18] have been reported to have related structures.…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with a previous Raman study by Torres Dias et al (2013), which suggested that Pbcn-Y 2 Mo 3 O 12 underwent a transition to a lower symmetry phase below 0.3 GPa. It is not surprising that this transition would occur at such a low pressure, as previous studies have shown that Sc 2 W 3 O 12 (Garg et al, 2005a; Varga et al, 2005b, 2006; Cetinkol et al, 2008), Sc 2 Mo 3 O 12 (Varga et al, 2005a) and Al 2 W 3 O 12 (Varga et al, 2005a) behave similarly and undergo this transition at 0.3 GPa, 0.25 GPa and 0.1 GPa, respectively. Initial unit cell parameters for the corresponding monoclinic unit cell were estimated based on the known transformation matrix (Evans and Mary, 2000), and combined with the atomic coordinates of α−Fe 2 Mo 3 O 12 as a starting model for a Rietveld refinement.…”
Section: Resultsmentioning
confidence: 88%
“…In contrast, the Cr 2 Mo 3 O 12 peaks start to become progressively diffuse above 5.5 GPa (scan 54), indicating the onset of disorder or amorphization. Many NTE materials have been reported to amorphize under pressure (Huang, 1998; Perottoni and da Jornada, 1998; Garg et al, 2001, 2005b; Liu et al, 2001, 2002; Secco et al, 2001, 2002a,b; Arora et al, 2004, 2005; Karmakar et al, 2004; Mukherjee et al, 2004; Paraguassu et al, 2004; Varga et al, 2005b; Gates et al, 2006; Keen et al, 2007; Catafesta et al, 2008; Cetinkol et al, 2009; Baiz et al, 2012; Torres Dias et al, 2013; Salke et al, 2018), especially under non-hydrostatic conditions, as their open frameworks allow for volume-reducing rotations of the constituent polyhedra. Under non-hydrostatic pressure, such random reorientations can become “frozen in” at relatively low pressures, resulting in progressive loss of long range order.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation